DISPERSI DENGAN METODE KERING UNTUK PENINGKATAN KONDUKTIVITAS KOMPOSIT LIMBAH GRAFIT/KARBON SERAT ALAM PADA APLIKASI PELAT BIPOLAR FUEL CELL - Insiyanda, Dita Rama; Chaer, Achmad (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2017)
Proton Exchange Fuel Cell Membrane (PEMFC) is the simplest type of fuel cell and is a promising alternative to power sources. The most important component of PEMFC is bipolar plate because 80% of total volume, 70% of total weight, and 60% of total production cost. Therefore, it is necessary for bipolar plates to be mass-produced to achieve the fulfillment of effectiveness and efficiency in the production of bipolar plates PEMFC. In this research, dry or dry method dispersion is used. The composites used are the polymer as matrix and graphite from factory waste and Carbon black (CB) from natural material of coconut fiber as an amplifier made from burning at 1300oC in inert condition. Then, the formation using hot press with pressure 55 tonf/s, 150oC for 60 minutes with dimension 5x5x (0,2-0,4) cm3. The highest result of this research is conductivity value of 20 S/cm. Thus, the dispersion by this dry method can be used as an alternative to increasing the conductivity in the manufacture of materials for PEMFC bipolar plate applications. Keywords: Dry Methods, Composites, Conductivity, Bipolar Plates, PEMFC.